An Experiential Study on Empathic Design in Interior Architecture Education - Melis Kocaoğlu; Halime Demirkan (Alanya Hamdullah Emin Paşa Üniversitesi, 2019)
Design students should be able to design living environments and products according to diverse users’ needs, problems and expectations. The aim of this research is to explore the role of empathy as a design learning tool in interior architecture education. Moreover, the intention is to determine and analyze the reflections after the role-playing technique is experienced. This study is conducted with the graduate design students and three tasks were assigned to them. In the first task, the students took visually impaired people’s role and acted in real-life activities in a café. Then, they expressed their role-playing reflections and design reflections through semi-structured interviews. Lastly, Verbal Protocol Analysis is used in determining and categorizing the relevant affective and cognitive empathic expressions that were recorded. Color and light, orientation, safety and accessibility were mostly expressed as design issues in reflections. Furthermore, findings indicated that cognitive empathic expressions were widely used than affective expressions.